2019
DOI: 10.1016/j.atherosclerosis.2019.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Cysteamine inhibits lysosomal oxidation of low density lipoprotein in human macrophages and reduces atherosclerosis in mice

Abstract: Background and aimsWe have shown previously that low density lipoprotein (LDL) aggregated by vortexing is internalised by macrophages and oxidised by iron in lysosomes to form the advanced lipid/protein oxidation product ceroid. We have now used sphingomyelinase-aggregated LDL, a more pathophysiological form of aggregated LDL, to study lysosomal oxidation of LDL and its inhibition by antioxidants, including cysteamine (2-aminoethanethiol), which concentrates in lysosomes by several orders of magnitude. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
(96 reference statements)
0
22
0
Order By: Relevance
“…Therefore, in our study, we selected LDL-C as the main research object to investigate the interaction between LDL-C and PDW. Oxidized LDL-C and platelet adhesion play an important role in endothelium-mediated vasodilation and hemodynamic changes in the peripheral circulation ( 14 , 15 ). In 2007, Hsiai and colleagues showed that apolipoprotein B-100 nitration is involved in hemodynamic changes, modulating the focal nature of atherogenesis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our study, we selected LDL-C as the main research object to investigate the interaction between LDL-C and PDW. Oxidized LDL-C and platelet adhesion play an important role in endothelium-mediated vasodilation and hemodynamic changes in the peripheral circulation ( 14 , 15 ). In 2007, Hsiai and colleagues showed that apolipoprotein B-100 nitration is involved in hemodynamic changes, modulating the focal nature of atherogenesis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that multiple antioxidants might be required for a disease in which multiple oxidants might be involved or that the trials were conducted with older patients in whom oxidative stress had become progressively less important with age [35,36]. The studies of a-tocopherol and LDL oxidation in vitro were carried out at pH 7.4, however, whereas it is possible that LDL oxidation in atherosclerotic lesions occurs in the lysosomes of macrophages at a pH of about 4.5 catalysed by iron [21,25]. We show here that in marked contrast to the expected inhibition by a-tocopherol of LDL oxidation by Cu 2þ at pH 7.4, a-tocopherol does not inhibit LDL oxidation by Cu 2þ or Fe 3þ at pH 4.5, although it inhibits LDL oxidation by higher concentrations of Fe 2þ at pH 4.5.…”
Section: Discussionmentioning
confidence: 99%
“…the large clinical trials of a-tocopherol were ineffective. It would be desirable to conduct clinical trials of antioxidants that accumulate in lysosomes and inhibit the oxidation of LDL at acidic pH, such as cysteamine [22][23][24][25].…”
Section: Aàtoc O þX ! Nonradical Productmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysteamine inhibits LDL oxidative reactions facilitated by free radicals and ameliorates lysosomal stresses and protects from proteolysis. 38 The oxidized LDL is associated with NF-kB activation. 39 Besides, LOX-1 may be involved in cyclic AMP (cAMP) signaling pathway regulation in oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%